A Retrospective Study of Postoperative Development of Implant-Induced Osteoporosis in Radial–Ulnar Fractures in Toy Breed Dogs Treated with Plate Fixation - Muroi, Norihiro; Shimada, Masakazu; Murakami, Sawako; Akagi, Hiroyuki; Kanno, Nobuo; Suzuki, Shuji; Harada, Yasuji; Orima, Hiromitsu; Hara, Yasushi (Veterinary and Comparative Orthopaedics and Traumatology, 2021)
Objective This study aimed to evaluate implant-induced osteoporosis (IIO) development in toy breed dogs treated using internal fixation with digital radiographs as the index of pixel values.Study Design There were 226 cases (236 limbs) of toy breed dogs with radial–ulnar fractures. Pixel values were measured on radiographs immediately, 2 weeks and 1 to 12 months after surgery. The ratio of pixel values (PVR) represented the bone mineral areal density based on the humeral condyle in the same image. The dogs were grouped based on the fixation methods, age and status of destabilization.Results There was a significant decrease in the PVR at 1 to 12 months postoperatively for all cases. There were not any significant differences in PVR of antebrachial fractures between those repaired with plates using locking head screws, cortex screws or a combination of locking and cortex screws. Implant-induced osteoporosis persisted at 1 to 12 months postoperatively in dogs aged ≧6 months, while the PVR increased after 3 months in dogs aged <6 months. Based on the destabilization method, there was a significant increase in the PVR at 3 months in the plate removal group.Conclusion This study suggests that IIO occurs in small dogs treated with plates and screws. Moreover, patients aged < 6 months showed an early postoperative recovery of bone mineral areal density. Further, screw and plate removal could contribute to the recovery of bone mineral areal density.
Keywords: implant-induced osteoporosis; radial-ulnar fractures; toy breed dogs; internal fixation; destabilization